As(III) removal from aqueous solution by adsorption - Singh D.B.; Prasad G.; Rupainwar D.C.; Singh V.N. (My University, 2025)
The removal of As(III) from aqueous solutions at different concentrations, pH and temperatures by haematite has been carried out successfully. The maximum removal was found to be 96 % at concentration 13.34 μmol L-1, temperature 20 °C and pH 7.0. The process of uptake follows first-order adsorption rate expression and obeys the Langmuir's model of adsorption. The removal of As(III) by haematite is also partially diffusion controlled and mass transfer coefficients, diffusion coefficients and thermodynamic parameters have been determined to explain the results. © 1988 Kluwer Academic Publishers.